Effect of chronic itching on quality of life in hemodialysis patients - Zeinab Shaki; Mohammad Reza Heidari; Mohsen Naseri; Anoshirvan Kazemnejad; Mohammad Kamalinejad; Hamid Reza Rostamani; Fatemeh Alijaniha (مجله دانشگاه علوم پزشکی گرگان, 2019)
Background and Objective: Chronic itching reduces the quality of life of patients undergoing hemodialysis. This study was done to determine the effect of chronic itching on the quality of life of patients under hemodialysis in north of Iran.